Active energy ray-curable adhesive and method for producing laminate
By using the active energy ray curing adhesives of (methyl) acrylate, polyol, and polytychenate, which have amino amin amin amin amin amin amino group, solve the problem of lack of membrane density that does not have a vulnerable layer, and reduce environmental protection in terms of environmental protection The use of solvents and volatile ingredients realizes efficient solidification and denseness.
Patent Information
- Application Number
- CN202380045202.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-22
- Filing Date
- 2023-06-22
- Publication Date
- 2025-01-21
AI Technical Summary
The conventional active energy ray curing adhesive exhibits poor versatility on films that do not have easy adhesive layers, and there are problems such as large amount of solvent use and large amounts of volatile components in terms of environmental protection and carbon neutrality.
An active energy ray-curable adhesive containing a 1-4 functional (meth)acrylate with a tertiary amino group, a polyol compound, and a polyisocyanate compound is used. It is instantly cured by irradiation with active energy rays and improves through the aging process. Tightness.
It is realized that regardless of whether the film has an easy-adhesive layer, it can show adhesion after active energy ray irradiation, and maintain sufficient adhesion after curing, reducing the amount of volatile components and solvents in the adhesive.
Smart Images

Figure BDA0005172113030000031 
Figure BDA0005172113030000041 
Figure BDA0005172113030000042
Abstract
Description
Technical Field
[0001] The present invention relates to an active energy ray-curable adhesive and a method for producing a laminate. Background Art
[0002] As the global population increases, the demand for flexible packaging, which is mainly used for packaging food and daily necessities, is expected to continue to grow. In flexible packaging, plastic films, metal foils, hot melt films (sealants), etc. that impart the characteristics required for various uses are usually attached to printed films from the perspectives of protecting the contents, improving impact resistance, and imparting heat sealability.
[0003] Typically, a laminated adhesive containing a polyisocyanate component and a polyol component is used to adhere other materials to a printed film to obtain a laminate and a packaged printed material having excellent solvent resistance even for highly polar solvents (Patent Document 1). However, since such a laminated adhesive contains a large amount of organic solvents represented by toluene, ethyl acetate, etc. during coating, a large amount of energy is required for drying and exhausting the solvent, and the environmental load is large. In addition, in recent years, in order to cope with environmental problems and carbon neutralization, it is also necessary to reduce the volatile components contained in the adhesive.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 5657990
[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 8-253736 Summary of the invention
[0008] Problems to be solved by the invention
[0009] Therefore, an active energy ray-curable adhesive composition comprising an aromatic acrylate monomer and a resin and forming a laminated film by electron beam irradiation has been proposed, as in Patent Document 2. However, since the active energy ray-curable adhesive composition can be used only for films having an easy-adhesion layer, it has a disadvantage of poor versatility.
[0010] Therefore, an object of the present invention is to provide an active energy ray-curable adhesive which cures instantaneously by irradiation with active energy rays and exhibits adhesion to a film having no easy-adhesion layer immediately after irradiation with active energy rays and exhibits sufficient adhesion even after curing.
[0011] Means of solving the problem
[0012] The present invention is an active energy ray-curable adhesive comprising a mono- to tetra-functional (meth)acrylate (A) having a tertiary amino group, a polyol compound (B), and a polyisocyanate compound (C).
[0013] The present invention is also a method for producing a laminate, which sequentially comprises the steps of bonding two or more films to each other by means of the active energy ray-curable adhesive of the present invention to form a laminate film, irradiating the laminate film with active energy rays, and aging the laminate film.
[0014] Effects of the Invention
[0015] The active energy ray-curable adhesive of the present invention is instantly cured by active energy ray irradiation to become non-tacky, and can exhibit adhesion immediately after irradiation with active energy rays even to a film having no easy-adhesion layer, and can also exhibit sufficient adhesion after curing. DETAILED DESCRIPTION
[0016] The present invention is described in detail below. It should be noted that, in the present invention, "above" means the same as or greater than the numerical value shown therein. In addition, "below" means the same as or less than the numerical value shown therein. In addition, "(meth)acrylate" refers to a general term including acrylate and methacrylate, and "(meth)acryloyl" refers to a general term including acryloyl and methacryloyl. In addition, "n-functional (meth)acrylate", "(meth)acrylate is n-functional" means that the number of (meth)acryloyl groups possessed by the (meth)acrylate is n.
[0017] The active energy ray-curable adhesive of the present invention contains a monofunctional to tetrafunctional (meth)acrylate having a tertiary amino group. Hereinafter, the (meth)acrylate is also referred to as (meth)acrylate (A).
[0018] The above-mentioned (meth) acrylate (A) is cured by irradiation with active energy rays to form a film. At the same time, the tertiary amino group interacts strongly with polar groups such as hydroxyl groups on the film surface, especially carboxyl groups, thereby improving the adhesion of the active energy ray-curable adhesive cured film to the film just after irradiation with active energy rays. This is the first time that the adhesion improvement effect is shown by having a tertiary amino group and a (meth) acryloyl group in the same compound. For example, when a tertiary amine without a (meth) acryloyl group is mixed with a (meth) acrylate and cured using active energy rays, the two compounds are not connected by a covalent bond, so the interaction between the (meth) acrylate crosslinked product in the cured film and the film surface will not become stronger, and the adhesion will not be improved.
[0019] Furthermore, the tertiary amino group contained in the (meth)acrylate (A) also acts as a catalyst in the urethane formation reaction between the polyol compound (B) and the polyisocyanate compound (C) described later, thereby promoting the reaction and shortening the curing time. Furthermore, compared with the case where only the catalyst coexists, the (meth)acrylate (A) is cured by active energy rays and enters the cured film through a covalent bond, so it also has the advantage of low migration.
[0020] The (meth)acrylate (A) is preferably monofunctional or difunctional. If the (meth)acrylate (A) is pentafunctional or more, the curing shrinkage of the active energy ray-curable adhesive is large, which may impair the adhesion.
[0021] As the (meth)acrylate (A), a compound represented by the following structural formula (1) is preferred.
[0022]
[0023] Among them, R 1 Represents H or methyl, R 2 represents a monovalent organic group having a (meth)acryloyl group, R 3 and R 4 Each independently represents a monovalent hydrocarbon group or a monovalent organic group containing a heteroatom.
[0024] Furthermore, as the (meth)acrylate (A), a compound represented by the following structural formula (2) or (3) is more preferred.
[0025]
[0026] Among them, R 1 Represents H or methyl, R 2 It represents a monovalent organic group having a (meth)acryloyl group.
[0027] As the (meth)acrylate (A), a compound represented by the following structural formula (4) is preferred.
[0028]
[0029] Wherein, X represents a nitrogen atom or a carbon atom, and R 1 Represents H or methyl, R 2 represents a monovalent organic group having a (meth)acryloyl group, R 3 and R 4 Each independently represents a monovalent hydrocarbon group or a monovalent organic group containing a heteroatom. 3 and R 4 Independently of each other or together they form a cyclic group.
[0030] The amine value of the (meth)acrylate (A) is preferably 80 mgKOH / g or more in order to strongly interact with various carboxyl groups and improve adhesion. In addition, in order to impart compatibility with other compounds, the amine value of the (meth)acrylate (A) is preferably 400 mgKOH / g or less, and more preferably 357 mgKOH / g or less.
[0031] Here, the amine value is expressed as the number of mg of potassium hydroxide equivalent to the hydrochloric acid required to neutralize the amino groups contained in 1 g of the sample, and can be measured by a method based on ASTM D2074.
[0032] The (meth)acrylate (A) preferably has a hydroxyl group, so that curability and adhesion can be more effectively improved by addition of a polyisocyanate compound (C) described later.
[0033] The above-mentioned (meth)acrylate (A) is obtained by subjecting primary or secondary amines to Michael addition reaction with multifunctional (meth)acrylate. Since (meth)acryloyl is an α-β unsaturated carbonyl compound, primary or secondary amines undergo 1,4 conjugated addition to form a 3-aminopropionate structure. When the amino group in the structure after the reaction is a secondary amino group, there is a possibility of further reaction and conversion to a tertiary amine. In addition, this reaction is a nucleophilic reaction, and the higher the nucleophilicity, the more it can be carried out under mild conditions. In addition, acids and bases can be used as catalysts to carry out the reaction at lower temperatures and higher speeds.
[0034] Specifically, when the Michael addition reaction is carried out, it is preferably carried out at a temperature below 20 to 100°C. In addition, in the reaction between the multifunctional (meth)acrylate and the amine, if all the (meth)acryloyl groups in each molecule react with the amine, it will not be cured by the active energy rays. Therefore, with respect to the equivalent ratio, it is preferred that the (meth)acryloyl group is in excess relative to the amino group. On the other hand, in order to increase the amine equivalent, it is also preferred to introduce multiple tertiary amino groups into the multifunctional (meth)acrylate with more than three functions, preferably more than four functions. In addition, if a polyamine with more than two functions is used as the raw material amine, it is possible to crosslink with the multifunctional (meth)acrylate and gel, so it is not preferred from the perspective of controlling the reaction. In addition, it is designed to slowly add the amines to the multifunctional (meth)acrylate by dripping or the like during the synthesis, and it is easy to obtain the desired (meth)acrylate (A) mentioned above, so it is preferred.
[0035] When the (meth)acrylate (A) has a hydroxyl group, either or both of the polyfunctional (meth)acrylate having a hydroxyl group as the raw material or the amine to be added may be used.
[0036] The polyfunctional (meth)acrylate as a raw material of the Michael addition reaction needs to have a (meth)acryloyl group remaining after the reaction, so in principle, a polyfunctional (meth)acrylate is used. Monofunctional (meth)acrylate is not suitable because the (meth)acryloyl group disappears during Michael addition.
[0037] Specific examples of the bifunctional (meth)acrylate as a raw material for the Michael addition reaction include 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, bisphenol A di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate. di(meth)acrylate, 1,3-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, glycerol di(meth)acrylate, pentaerythritol di(meth)acrylate, diglycerol di(meth)acrylate, di(trimethylolpropane) di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethylene oxide adducts, propylene oxide adducts, tetraethylene oxide adducts thereof, and the like.
[0038] Examples of the trifunctional (meth)acrylate as a raw material for the Michael addition reaction include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, di(trimethylolpropane) tri(meth)acrylate, glycerol tri(meth)acrylate, isocyanuric acid tri(meth)acrylate, di(trimethylolpropane) tri(meth)acrylate, and ethylene oxide adducts, propylene oxide adducts, and tetraethylene oxide adducts thereof.
[0039] Examples of the tetrafunctional (meth)acrylate as a raw material for the Michael addition reaction include di(trimethylolpropane)tetra(meth)acrylate, diglycerol tetra(meth)acrylate, di(trimethylolpropane)tetra(meth)acrylate, and ethylene oxide adducts and propylene oxide adducts thereof.
[0040] Examples of the pentafunctional or higher-functional (meth)acrylates as raw materials for the Michael addition reaction include dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and their ethylene oxide adducts, propylene oxide adducts, etc. In particular, when using a hexafunctional or higher-functional (meth)acrylate, it is preferred to set the equivalent ratio so that the difunctional or higher-functional amines react.
[0041] Specific examples of primary amines as raw materials for the Michael addition reaction include monoamines such as alkylamines having 1 to 20 carbon atoms, alkanolamines having 1 to 10 carbon atoms, and derivatives thereof. Specific examples of secondary amines include N-alkyl substituted products (having 1 to 20 carbon atoms) of the above monoamines, N-alkanol substituted products (having 1 to 10 carbon atoms) of the above monoamines, cyclic amines such as morpholine, pyrrolidine, and piperidine, derivatives thereof other than N-substituted products, 1H-azoles such as 1H-triazole, 1H-benzotriazole, 1H-benzimidazole, 1H-imidazole, and 1H-pyrazole, and derivatives thereof other than 1H-substituted products. Polyamines thereof may also be used, but in this case, control is required to suppress gelation.
[0042] Among these primary and secondary amines, amines with less odor are preferred, and octadecylamine and diethanolamine are particularly preferred because they are raw materials that can be used in food packaging regulations such as the Swiss Ordinance.
[0043] In addition, adducts of 1H-azoles having a heterocyclic ring such as 1H-triazole, 1H-benzotriazole, 1H-benzimidazole, and 1H-imidazole are particularly preferred because they have a particularly high effect of improving adhesion.
[0044] Among these primary and secondary amines, highly nucleophilic aliphatic amines undergo Michael addition reaction under relatively mild conditions of 20 to 60° C. On the other hand, the reaction of less nucleophilic aromatic amines proceeds slowly, and it is preferred to heat to 80 to 100° C. for the Michael addition reaction.
[0045] When the (meth)acrylate (A) is synthesized using the above-mentioned particularly preferred diethanolamine, the compound represented by the above structural formula (2) is formed, and when the (meth)acrylate (A) is synthesized using octadecylamine, the compound represented by the above structural formula (3) is formed. In addition, when the (meth)acrylate (A) is synthesized using 1H-azoles, the compound represented by the above structural formula (4) is formed.
[0046] As the (meth)acrylate (A), commercially available products can be used, and examples thereof include "EBECRYL" (registered trademark) LEO 10101, "EBECRYL" (registered trademark) LEO 10551, "EBECRYL" (registered trademark) LEO 10552, "EBECRYL" (registered trademark) LEO 10553, "EBECRYL" (registered trademark) LEO 10554, "EBECRYL" (registered trademark) LEO 10555, and "EBECRYL" (registered trademark) LEO 10556. 10553, EBECRYL" (registered trademark) 80, EBECRYL" (registered trademark) 81, EBECRYL" (registered trademark) 83, EBECRYL" (registered trademark) 85, EBECRYL" (registered trademark) 880, EBECRYL" (registered trademark) 7100, ETERCURE" (registered trademark) 63922 manufactured by Eternal, CN549NS, CN550, CN551NS manufactured by Sartomer, AgiSyn" (registered trademark) 701, AgiSyn" (registered trademark) 701P, AgiSyn" (registered trademark) 703, AgiSyn" (registered trademark) 703TF manufactured by DSM, Miramer" (registered trademark) AS1000, Miramer" (registered trademark) AS3500, Miramer" (registered trademark) LR3600 manufactured by Miwon, Photocryl A104, Photocryl DP143, etc.
[0047] The molecular weight of the (meth)acrylate (A) is preferably 1000 or less from the viewpoint of improving the curability to active energy rays and suppressing the viscosity increase of the active energy ray-curable adhesive of the present invention when it does not have a hydroxyl group. It is more preferably 600 or less. On the other hand, when it has a hydroxyl group, the weight average molecular weight is preferably 3000 or more and 100000 or less from the viewpoint of improving the curability and adhesion by addition with the polyisocyanate compound (C).
[0048] The (meth)acrylate (A) is preferably contained in the active energy ray-curable adhesive in an amount of 10% by mass or more and 40% by mass or less.
[0049] When the content of the (meth)acrylate (A) is 10% by mass or more, more preferably 20% by mass or more, film adhesion improves.
[0050] By making the content of the above-mentioned (meth)acrylate (A) 40 mass % or less, it is possible to cope with the case where other functional materials are included depending on the application, the case where an initiator or a sensitizer is added according to the active energy ray source, the case where a resin, an oligomer, an auxiliary agent, etc. are added to adjust the viscoelasticity of the active energy ray-curable adhesive, etc.
[0051] The active energy ray-curable adhesive of the present invention contains a polyol compound (B). The polyol compound (B) is a compound having two or more hydroxyl groups.
[0052] Specific examples of the polyol compound (B) include neopentyl glycol, 1,3-butanediol, 1,4-butanediol, tripropylene glycol, tetramethylene glycol, glycerol, trimethylolpropane, pentaerythritol, di(trimethylolpropane), diglycerol, dipentaerythritol, ethylene oxide adducts, propylene oxide adducts, tetraethylene oxide adducts, and lactone adducts.
[0053] In addition, the polyol compound (B) is preferably a polyester polyol from the viewpoint of improving the heat resistance of the active energy ray-curable adhesive and providing resistance to boiling and retorting treatments.
[0054] The polyester structure in the polyester polyol is obtained by reacting a dicarboxylic acid derivative with a glycol. Specific examples of the dicarboxylic acid derivative include phthalic acid, isophthalic acid, terephthalic acid, adipic acid, oxalic acid, maleic acid, fumaric acid, sebacic acid, etc. A polyester polyol having a polyester structure formed by reacting these with a glycol and having a hydroxyl terminal can be used.
[0055] In addition, polyol compounds with carbonate structures can also be used. Specifically, for example, pentamethylene carbonate diol, hexamethylene carbonate diol, hexane carbonate diol, decane carbonate diol, etc. can be cited. In addition, these polyol compounds can be used 1 or in combination of 2 or more.
[0056] The molecular weight of the polyol compound (B) is preferably 500 or more, more preferably 1000 or more, and even more preferably 2000 or more, from the viewpoint of improving adhesion due to a high molecular weight.
[0057] On the other hand, from the viewpoint of improving the fluidity of the adhesive and thus improving coating properties, the molecular weight of the polyol compound (B) is preferably 10,000 or less, more preferably 7,000 or less, and even more preferably 5,000 or less.
[0058] The active energy ray-curable adhesive of the present invention contains a polyisocyanate compound (C). The polyisocyanate compound (C) refers to a compound having two or more isocyanate groups, and is a component that is converted to a high molecular weight by an addition reaction. In the active energy ray-curable adhesive of the present invention, polyurethane is formed by mixing and reacting the polyol compound (B) and the polyisocyanate compound (C).
[0059] In particular, in the polyurethane formation reaction, the tertiary amino group contained in the (meth)acrylate (A) also has a catalyst function, thereby promoting the reaction and shortening the curing time. Furthermore, compared with the case where only the catalyst coexists, the (meth)acrylate (A) is cured by active energy rays and enters the cured film through a covalent bond, so it also has the advantage of low migration.
[0060] As the specific example of the above-mentioned polyisocyanate compound (C), toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, 4,4-methylenebiscyclohexyl diisocyanate, hydrogenated xylylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, trimethyl hexamethylene diisocyanate etc. can be listed. Urate modified products, adduct modified products, biuret modified products, allophanate modified products etc. of these polyisocyanate compounds can also be used. These diisocyanates can be used one or in combination of two or more.
[0061] From the perspective of suppressing dissolution when remaining in the cured product of the adhesive, the weight average molecular weight of the polyisocyanate compound (C) is preferably 500 or more, more preferably 1000 or more, and further preferably 2000 or more. On the other hand, from the perspective of improving the fluidity of the adhesive and thus improving the coating property, the weight average molecular weight of the polyisocyanate compound (C) is preferably 10000 or less, more preferably 7000 or less, and further preferably 5000 or less.
[0062] The total content of the polyol compound (B) and the polyisocyanate compound (C) in the active energy ray-curable adhesive of the present invention is preferably 50% by mass or more, and more preferably 60% by mass or more, from the perspective of improving the adhesion of the final laminated film and further softening the cured product of the active energy ray-curable adhesive. In addition, in order to reduce the curability to active energy rays and the viscosity of the adhesive, it is preferably 80% by mass or less, and more preferably 70% by mass or less.
[0063] The equivalent ratio of the polyol compound (B) to the polyisocyanate compound (C) is preferably such that the content of the isocyanate group of the polyisocyanate compound is 0.8 mol or more and 1.2 mol or less per 1.0 mol of the hydroxyl group of the polyol compound (B).
[0064] In addition, when the (meth)acrylate (A) has a hydroxyl group, the content of the isocyanate group of the polyisocyanate compound is preferably 0.8 mol or more and 1.2 mol or less relative to 1.0 mol of the total of the hydroxyl group of the (meth)acrylate (A) and the hydroxyl group of the polyol compound (B). The closer the equivalent ratio is, the easier the chain extension reaction is to proceed, and the higher the molecular weight of the obtained polyurethane can be, so that the adhesion is improved.
[0065] The active energy ray-curable adhesive of the present invention preferably further comprises a multifunctional (meth)acrylate having a weight average molecular weight of less than 3000 and containing no amino group. Hereinafter, the (meth)acrylate is also referred to as (meth)acrylate (D). The (meth)acrylate (D) is cured by irradiation with active energy rays, which helps to form a film.
[0066] As the (meth)acrylate (D), from the perspective of curability, a highly reactive substance is preferred. From the perspective of safety and environment, a low volatility is preferred. Low volatility means that the weight loss rate after heating at 110° C. for 1 hour is less than 1% by weight as defined in Method 24 of the U.S. Environmental Protection Agency (EPA).
[0067] Specific examples of such (meth)acrylates (D) include bifunctional (meth)acrylates (D) such as 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, bisphenol A di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and polyoxyethylene glycol di(meth)acrylate. Propylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, glycerol di(meth)acrylate, pentaerythritol di(meth)acrylate, diglycerol di(meth)acrylate, di(trimethylolpropane) di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethylene oxide adducts, propylene oxide adducts, tetraethylene oxide adducts thereof, and the like.
[0068] Examples of the trifunctional (meth)acrylate (D) include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, di(trimethylolpropane) tri(meth)acrylate, glycerol tri(meth)acrylate, isocyanuric acid tri(meth)acrylate, di(trimethylolpropane) tri(meth)acrylate, and ethylene oxide adducts, propylene oxide adducts, and tetraethylene oxide adducts thereof.
[0069] Examples of the tetrafunctional (meth)acrylate (D) include di(trimethylolpropane)tetra(meth)acrylate, diglycerol tetra(meth)acrylate, di(trimethylolpropane)tetra(meth)acrylate, and ethylene oxide adducts and propylene oxide adducts thereof.
[0070] Examples of the pentafunctional or higher-functional (meth)acrylate (D) include dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ethylene oxide adducts and propylene oxide adducts thereof.
[0071] The active energy ray-curable adhesive of the present invention preferably contains a compound having a carboxyl group and a weight average molecular weight of 3000 or more and 100000 or less. Hereinafter, the compound is also referred to as compound (E). The tertiary amino group of the (meth)acrylate (A) interacts with the carboxyl group of the high molecular weight compound (E), thereby improving the film-forming property and film strength of the cured film of the active energy ray-curable adhesive.
[0072] In the active energy ray-curable adhesive of the present invention, the number of moles of the carboxyl groups derived from the compound (E) is n c (E) and the number of moles of amino groups derived from (A) a (A) ratio n c (E) / n a (A) is preferably 0.01 or more and 0.50 or less. c (E) / n a (A) is 0.01 or more, which can effectively improve the film-forming property and film strength of the cured film of the active energy ray-curable adhesive. c (E) / n a (A) is 0.50 or less, more preferably 0.30 or less, and further preferably 0.15 or less, and the adhesion due to the interaction between the tertiary amino group and the polar group on the film surface can be effectively improved.
[0073] The compound (E) preferably has a (meth)acryloyl group and / or a vinyl group. The compound (E) also interacts with the (meth)acrylate (A) to form crosslinks. Therefore, by providing the compound (E) with the photosensitive group as described above, the curability to active energy rays is improved, and the strength and adhesion of the cured film are also improved.
[0074] The active energy ray-curable adhesive of the present invention may contain a photopolymerization initiator depending on the active energy ray source. Examples of the photopolymerization initiator include α-aminoalkylphenones, thioxanthones, benzyl ketals, and acylphosphine oxides.
[0075] The active energy ray-curable adhesive of the present invention may contain additives such as wax, a pigment dispersant, a defoaming agent, and a leveling agent as other components.
[0076] The active energy ray curing adhesive of the present invention is preferably substantially free of solvent and diluent. The solvent referred to here refers to a solvent that does not contain a (meth)acryloyl group and is liquid at 1 atmosphere and 25°C. In addition, substantially free of solvent and diluent referred to here means that the total content of solvent and diluent in the active energy ray curing adhesive is less than 0.1% by mass. By making the active energy ray curing adhesive of the present invention substantially free of solvent, the curability of the adhesive to active energy rays can be improved. In addition, the situation where the solvent is transferred to the contents through the printed film can be suppressed.
[0077] The acryl equivalent of the active energy ray-curable adhesive of the present invention is preferably 300 g / eq or more and 1000 g / eq or less. By making the acryl equivalent of 300 g / eq or more, more preferably 500 g / eq or more, the storage stability is improved. In addition, by making the acryl equivalent of 1000 g / eq or less, more preferably 800 g / eq or less, the curability based on active energy rays becomes good. It should be noted that in the present invention, the acryl equivalent represents the number of grams of active energy ray-curable adhesive required for the amount of (meth)acryloyl groups contained in the active energy ray-curable adhesive to reach 1 mole (unit: g / eq).
[0078] Next, a method for producing the active energy ray-curable adhesive of the present invention will be described.
[0079] The active energy ray-curable adhesive of the present invention can be obtained by mixing the (meth)acrylate (A), the polyol compound (B), the polyisocyanate compound (C), and, if necessary, the (meth)acrylate (D), the compound (E), and other components at room temperature to 80°C.
[0080] After or during mixing, degassing is also preferably performed under vacuum or reduced pressure conditions.
[0081] It should be noted that when the above-mentioned polyol compound (B) is mixed with the above-mentioned polyisocyanate compound (C), a polyurethane formation reaction will occur and begin to thicken. Therefore, in practical applications, it is preferred to separately prepare the α liquid of the above-mentioned polyisocyanate compound (C) and the β liquid mixed with other components, mix the two liquids just before use, and use them as an adhesive in a laminator.
[0082] The first embodiment of the method for manufacturing a laminate of the present invention comprises, in sequence, a lamination step of bonding the same or two or more films to each other by means of the active energy ray-curable adhesive of the present invention to form a laminate film, an irradiation step of irradiating the laminate film with active energy rays, and an aging step of aging the laminate film.
[0083] In the lamination step, the active energy ray-curable adhesive of the present invention is applied to any one of the films, and the other film is bonded to the wet coated film to obtain a laminated film. One film is preferably a printed material with ink, and the other film is preferably a sealant.
[0084] In addition, the second embodiment of the method for manufacturing a laminate of the present invention sequentially comprises a step of applying an active energy ray-curable adhesive on a film, an irradiation step of irradiating the film coated with the adhesive with active energy rays, a lamination step of bonding the same or different types of films to each other on the film coated with the adhesive to form a laminated film, and an aging step of aging. By irradiating the film coated with the adhesive with active energy rays, the other film to be bonded is not separated, so the other film will not be damaged by the improvement of curability or the energy ray source, which is preferred.
[0085] Examples of the film used in the present invention include polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyesters such as polylactic acid, polyamides, polyimides, polyalkyl (meth)acrylates, polystyrene, poly-α-methylstyrene, polycarbonates, polyvinyl alcohols, polyvinyl acetals, polyvinyl chlorides, and polyvinylidene fluoride.
[0086] Furthermore, these films may be used in which a vapor-deposited thin film layer made of a metal such as aluminum oxide or a metal compound is further provided.
[0087] The film is preferably subjected to a corona treatment on its surface in order to increase the polar functional groups on the film surface and improve the adhesion with the active energy ray-curable adhesive. In addition, when the film is a printed material, the surface of the solid color portion is preferably subjected to a corona treatment.
[0088] The film having the surface subjected to the corona treatment may be a ready-made product or a film subjected to the in-line corona treatment before printing or lamination.
[0089] The film may have an easy-adhesion coating layer, but this will increase the cost. The active energy ray-curable adhesive of the present invention is preferred because it can exhibit sufficient adhesion even to a film without an easy-adhesion layer.
[0090] As the shape of the film, any of a single sheet and a roll film may be used. When a film for flexible packaging is used, it is preferred to use a roll film and perform coating and printing in a roll-to-roll method.
[0091] In the irradiation step, the (meth)acryloyl group reacts by irradiation with the active energy ray, and crosslinking is performed by covalent bonds, whereby the active energy ray-curable adhesive is instantly cured.
[0092] Examples of the active energy ray source used in the irradiation step include ultraviolet rays, electron beams, and gamma rays.
[0093] If ultraviolet rays are used, it is preferred to use ultraviolet irradiation devices such as high-pressure mercury lamps, xenon lamps, metal halide lamps, and light-emitting diodes (LEDs). Among them, LED lamps are preferred because they save power and produce less ozone. As for the wavelength of LED, a bright line of 350 to 420 nm is preferred from the perspective of power saving and cost reduction.
[0094] If it is an electron beam, the (meth) acryloyl group is directly excited by free radicals, and free radical polymerization is carried out in the active energy ray-cured adhesive to form a film. In addition, the electron beam has high permeability and can also act on the film. In the case of a polyolefin film, free radicals are easily generated, causing crosslinking, decomposition and other reactions between molecules, and free radical polymerization is carried out between the active energy ray-cured adhesive / film, thereby forming a covalent bond between the active energy ray-cured adhesive / film, which can show higher adhesion. In particular, it is preferred to use an electron beam with a low acceleration voltage because there are no special qualification requirements and easy operation when using it. The penetration depth of the electron beam is determined by the acceleration voltage. Therefore, from the perspective of sufficient permeability and damage to the film, the acceleration voltage is preferably 50kV to 300kV. In addition, since the amount of free radical seeds generated in the target substance increases, the damage to the film also increases on the other hand, so the irradiation dose of the electron beam is preferably 10kGy or more and 100kGy or less.
[0095] In the aging step, the polyol compound (B) and the polyisocyanate compound (C) in the adhesive react with each other by heating in an environment within a range of 40° C. to 60° C., thereby increasing the molecular weight and further improving the adhesion.
[0096] Example
[0097] The present invention will be specifically described below by way of examples, but the present invention is not limited thereto.
[0098] [Measurement / Evaluation Method]
[0099] (1) Amine value
[0100] The amine value is measured by a method based on ASTM D2074. An ethanol solution of each (meth)acrylate (A) is prepared, and a potentiometric titration apparatus is used to measure the potential difference with a 0.2N hydrochloric acid ethanol solution, and the inflection point of the obtained titration curve is taken as the end point. Then, the amount of hydrochloric acid consumed until the inflection point is converted into the equivalent of potassium hydroxide.
[0101] (2) Acryloyl equivalent
[0102] A deuterated acetone solution with a concentration of 1% by mass of each active energy ray-curable adhesive was prepared, and 0.05% by mass of tetramethylsilane was added as an internal standard for end-capping. 1 H-NMR measurement: The molar ratio was determined from the integrated ratio of the (meth)acryloyl peak (δ: 5.8 to 6.5) and the methyl peak of internal standard tetramethylsilane (δ: -0.05 to +0.05), and the number of moles of acryloyl in the adhesive was calculated to calculate the acryloyl equivalent.
[0103] (3) Weight average molecular weight
[0104] The weight average molecular weight is a value measured by gel permeation chromatography (GPC) using tetrahydrofuran as a mobile phase at a column temperature of 40° C. Shodex KF-803 was used as a column, and the weight average molecular weight was calculated in terms of polystyrene.
[0105] (4) Coating appearance
[0106] The appearance of the coated material of the active energy ray-curable adhesive obtained in each of the Examples and Comparative Examples was visually evaluated as follows.
[0107] A: No bubbles were observed and the appearance was good.
[0108] B: Few bubbles were observed.
[0109] C: Bubbles or grapefruit peels were observed everywhere.
[0110] (5) Peel strength
[0111] The samples obtained in each example and comparative example were cut into strips with a width of 15 mm, and the peel strength was measured when peeled at 90° at 300 mm / min using a Tensilon universal testing machine (RTG-1210 manufactured by Orientec Corporation).
[0112] The peel strength of the sample immediately after curing with active energy rays was evaluated as “initial adhesion”. In addition, the peel strength of the sample after aging at 40° C. for 72 hours (after curing) was evaluated as “adhesion after curing”.
[0113] Regarding initial adhesion, if the peel strength was less than 1.0 N / 15 mm, the adhesion was judged to be insufficient, if it was 1.0 N / 15 mm or more and less than 2.0 N / 15 mm, the adhesion was judged to be good, and if it was 2.0 N / 15 mm or more, it was judged to be excellent.
[0114] Regarding the adhesion after curing, if the peel strength is less than 3.0 N / 15 mm, the adhesion is judged to be insufficient, if it is 3.0 N / 15 mm or more and less than 4.0 N / 15 mm, the adhesion is judged to be good, and if it is 4.0 N / 15 mm or more, the adhesion is judged to be excellent.
[0115] (6) Failure mode
[0116] In the peeling test after curing (5) above, the peeling state (failure mode) is also observed. In a multilayer structure sample, the interlayer where failure occurs during peeling corresponds to the weakest adhesion point. Evaluation is performed according to the following A to C.
[0117] A: Membrane rupture.
[0118] B: The active energy ray-curable adhesive layer suffers cohesive failure.
[0119] C: Peeling occurred between the film / active energy ray-curable adhesive layers.
[0120] Here, the "active energy ray-curable adhesive layer" refers to a layer formed by curing an active energy ray-curable adhesive. The above A is most preferred, the above B is second most preferred, and the above C is not preferred.
[0121] [(Meth)acrylate (A)]
[0122] In the following, the corresponding primary or secondary amine and the polyfunctional (meth)acrylate were weighed and mixed and stirred at 60° C. for 4 hours using a mechanical stirrer to perform a Michael addition reaction to obtain the corresponding (meth)acrylate (A).
[0123] (A)-1: A di- to tri-functional (meth)acrylate obtained by subjecting pentaerythritol triacrylate (Miramer (registered trademark) M340 manufactured by MIWON) to a Michael addition reaction with diethanolamine (manufactured by Waken Chemical Co., Ltd.) at an equivalent ratio of 5:2. It has a hydroxyl group, an amine value of 159 mgKOH / g, and a weight average molecular weight of 360.
[0124] (A)-2: A 2- to 3-functional (meth)acrylate obtained by subjecting ditrimethylolpropane tetraacrylate (Miramer (registered trademark) M410 manufactured by MIWON) to a Michael addition reaction with di(2-ethylhexyl)amine (manufactured by Waken Chemical Co., Ltd.) at an equivalent ratio of 2:1. It has no hydroxyl group, an amine value of 118 mg KOH / g, and a weight average molecular weight of 590.
[0125] (A)-3: A bifunctional (meth)acrylate obtained by subjecting EO-modified trimethylolpropane triacrylate (Miramer (registered trademark) M3190 manufactured by MIWON) to a Michael addition reaction with di(2-ethylhexyl)amine (manufactured by Waken Chemical Co., Ltd.) at an equivalent ratio of 2:1. Contains no hydroxyl group, has an amine value of 79 mgKOH / g, and a weight average molecular weight of 810.
[0126] (A)-4: A mono- or di-functional (meth)acrylate obtained by subjecting tricyclodecane dimethanol diacrylate (manufactured by Dicel Ornex, "EBECRYL" (registered trademark) 130) and octadecylamine (manufactured by TCI Corporation) to a Michael addition reaction at an equivalent ratio of 2:1. It has no hydroxyl group, an amine value of 96 mgKOH / g, and a weight average molecular weight of 420.
[0127] (A)-5: dimethylaminoethyl methacrylate (manufactured by TCI Corporation). (A)-5 is a monofunctional (meth)acrylate. It has no hydroxyl group, an amine value of 357 mgKOH / g, and a weight average molecular weight of 160.
[0128] (A)-6: A 4-5-functional (meth)acrylate obtained by subjecting dipentaerythritol hexaacrylate (Miramer (registered trademark) M600 manufactured by MIWON) to Michael addition reaction with 1H-benzotriazole (manufactured by Waken Chemical Co., Ltd.) at an equivalent ratio of 3:1. It has no hydroxyl group, an amine value of 135 mgKOH / g, and a weight average molecular weight of 630.
[0129] (A)-7: A mono- to tri-functional (meth)acrylate obtained by subjecting pentaerythritol triacrylate (Miramer (registered trademark) M340 manufactured by MIWON), dimethylaminoethyl methacrylate (TCI (Inc.)) and polyetheramine (JEFFAMINE (registered trademark) D-2000 manufactured by HUNTSMAN) to a Michael addition reaction at an equivalent ratio of 1:3:1. Contains hydroxyl groups, amine value 91 mgKOH / g, weight average molecular weight 3200.
[0130] [Polyol compound (B)]
[0131] (B)-1: Mitsui Chemicals, "Takerk" (registered trademark) A-244B
[0132] (B)-2: Mitsui Chemicals, “Takeruck” (registered trademark) A-246B.
[0133] [Polyisocyanate compound (C)]
[0134] (C)-1: Mitsui Chemicals, "Takenet" (registered trademark) A-244A
[0135] (C)-2: Mitsui Chemicals, “Takenet” (registered trademark) A-246A.
[0136] [(Meth)acrylate (D)]
[0137] (D)-1: EO-modified trimethylolpropane triacrylate (Miramer (registered trademark) M3190 manufactured by MIWON Corporation)
[0138] (D)-2: ditrimethylolpropane tetraacrylate (manufactured by MIWON Corporation, "Miramer" (registered trademark) M410).
[0139] [Compound (E)]
[0140] (E)-1: Acrylic resin having a photosensitive group and a carboxylic acid (TWR-1001 manufactured by Toray Industries, Inc.), molecular weight: 30,000, acid value: 105 mgKOH / g.
[0141] (E)-2: Acrylic resin having carboxylic acid (TWR-3001 manufactured by Toray Industries, Inc.) Molecular weight: 27,000, acid value: 200 mgKOH / g.
[0142] [Other (meth)acrylates]
[0143] (F)-1: A trifunctional or higher-functional (meth)acrylate having a tertiary amino group obtained by subjecting dipentaerythritol hexaacrylate (Miramer (registered trademark) M600 manufactured by MIWON) and di(2-ethylhexyl)amine (manufactured by Waken Chemical Co., Ltd.) to a Michael addition reaction at an equivalent ratio of 6:1. Amine value: 66 mgKOH / g.
[0144] [Other added ingredients]
[0145] Photopolymerization initiator: bis(2,4,6-trimethylbenzoyl)-phenyl-phosphine oxide (manufactured by BASF, "ILGACURA" (registered trademark) 819).
[0146] Solvent: ethyl acetate (manufactured by Waken Chemical Co., Ltd.).
[0147] [Active energy ray-curable adhesive]
[0148] The respective materials were weighed according to the composition shown in Table 1, and mixed and dissolved using a mixer (manufactured by Shinki Co., Ltd.), thereby obtaining an active energy ray-curable adhesive.
[0149]
[0150] [membrane]
[0151] Film 1: PET film (E5102, manufactured by Toyobo Co., Ltd.) with a thickness of 12 μm and having a corona-treated layer.
[0152] Film 2: 12 μm thick PET film (FS2000, manufactured by FTAMURA CHEMICAL CO., LTD.), without surface treatment.
[0153] Film 3: A polyamide film having a thickness of 15 μm (manufactured by UNITICA CO., LTD., ON), having a corona treatment layer.
[0154] Film 4: a barrier film / PET film laminate having a thickness of 12 μm (manufactured by Toray Film Manufacturing Co., Ltd., 1011HG SBR2), without a corona treatment layer.
[0155] Film 5: OPP film with a thickness of 20 μm (manufactured by Toyobo Co., Ltd., P2111), having a corona treatment layer.
[0156] Film 6: PET film having a thickness of 12 μm (manufactured by Toray Industries, Ltd., “LumiLa” (registered trademark) S10), without surface treatment.
[0157] [Method 1 for producing laminate]
[0158] For each film, the coating amount was set to about 2.0 g / m 2 After applying various active energy ray curing adhesives in a manner, a sealant (unstretched polypropylene film (CPP), manufactured by Toray Film Processing Co., Ltd., ZK-207, thickness 60 μm) was laminated. Then, an electron beam irradiation device (manufactured by Iwasaki Electric Co., Ltd., EC250 / 30 / 90LS) was used to irradiate electron beams from one side of the substrate film at an acceleration voltage of 110 kV and an irradiation dose of 30 kGy, thereby curing the adhesive. Then, the film was cured at 40°C for 72 hours.
[0159] [Method 2 for producing laminate]
[0160] For each film, the coating amount was set to about 2.0 g / m 2After applying various active energy ray-curable adhesives in a manner, a sealant (unstretched polypropylene film (CPP), manufactured by Toray Film Processing Co., Ltd., ZK-207, thickness 60 μm) was laminated. Then, a light-emitting diode ultraviolet irradiation device (manufactured by Panasonic Debius SUNX Co., Ltd., UD90) was used to irradiate from one side of the substrate film at an intensity of 8 W / cm 2 , irradiate with LED-UV at a wavelength of 385 nm to cure the adhesive, and then cure at 40°C for 72 hours.
[0161] [Method 3 for producing laminate]
[0162] Each film was subjected to a corona treatment using a corona treatment apparatus (TEC-4AX, manufactured by Kasuga Electric Co., Ltd.) at a discharge amount E of 200 W·min / m 2 Then, the coating amount was adjusted to about 2.0 g / m 2 Various active energy ray curing adhesives were applied in a manner, and a laminated sealant (unstretched polypropylene film (CPP), manufactured by Toray Film Processing Co., Ltd., ZK-207, thickness 60 μm) was applied. Then, an electron beam irradiation device (manufactured by Iwasaki Electric Co., Ltd., EC250 / 30 / 90LS) was used to irradiate electron beams at an acceleration voltage of 110 kV and an irradiation dose of 30 kGy from one side of the substrate film to cure the adhesive. Then, the film was cured at 40°C for 72 hours.
[0163] [Method 4 for producing laminate]
[0164] For each film, the coating amount was set to about 2.0 g / m 2 After applying various active energy ray curing adhesives in a manner, an electron beam irradiation device (EC250 / 30 / 90LS manufactured by Iwasaki Electric Co., Ltd.) was used to perform electron beam irradiation with an acceleration voltage of 110 kV and an irradiation dose of 30 kGy from one side of the adhesive to cure the adhesive. Then, a sealant (unstretched polypropylene film (CPP), manufactured by Toray Film Processing Co., Ltd., ZK-207, thickness 60 μm) was laminated. Then, the film was cured at 40°C for 72 hours.
[0165] [Example 1]
[0166] Using active energy ray-curable adhesive 1 as active energy ray-curable adhesive and using film 1 as film, a laminate was produced by the manufacturing method 1 of the laminate. Regarding peel strength, the initial adhesion was also good, which was 1.8N / 15mm, and the adhesion after curing was also excellent, which was 4.5N / 15mm. In addition, the failure mode was also good (A), and the appearance of the coating was also good. The results are shown in Table 2.
[0167] [Examples 2 to 15 and Comparative Examples 1 to 3]
[0168] Using active energy ray-curable adhesives 2 to 15 and 17 to 19 as active energy ray-curable adhesives and using film 1 as a film, a laminate was produced by the manufacturing method 1 of a laminate. In Examples 2 to 15, the peel strength was good or above. By increasing the (meth)acrylate (A) component, a tendency for the initial adhesion to improve can be found, but the amount of the polyol compound (B) and the polyisocyanate compound (C) components is reduced, and therefore, a tendency for the adhesion after curing to decrease can be found. In Comparative Examples 1 to 3, if there is no (meth)acrylate (A) component, the initial adhesion is insufficient, and if there is no polyol compound (B) and the polyisocyanate compound (C) component, the adhesion after curing is insufficient. The results are shown in Table 2.
[0169] [Examples 16 to 20]
[0170] Using active energy ray-curable adhesive 1 as the active energy ray-curable adhesive and using films 2 to 6 as the films, a laminate was produced by the manufacturing method 1 of a laminate. Regarding the peel strength, the initial adhesion and the adhesion after curing were all good or better, and particularly, the film subjected to the corona treatment achieved an excellent result. The results are shown in Table 3.
[0171] [Examples 21 and 22]
[0172] Active energy ray-curable adhesive 16 was used as the active energy ray-curable adhesive, and films 1 and 2 were used as the films, and a laminate was produced by the manufacturing method 2 of the laminate and by UV curing. For any film, the initial adhesion and the adhesion after curing were both good or above in terms of peel strength, and the corona-treated film 1 was particularly good. The results are shown in Table 3.
[0173] [Examples 23 and 24]
[0174] Using active energy ray-curable adhesive 1 as the active energy ray-curable adhesive and using films 2 and 4 as the films, a laminate was produced by the laminate production method 3. By performing the corona treatment, both the initial adhesion and the adhesion after curing were improved for any of the films, and the laminate peel strength was excellent. The results are shown in Table 3.
[0175] [Example 25]
[0176] Using active energy ray-curable adhesive 1 as the active energy ray-curable adhesive and film 4 as the film, a laminate was produced by the manufacturing method 4 of the laminate. By implementing electron beam irradiation before lamination, it was observed that the initial adhesion due to the accelerated curing was improved. The final lamination peel strength was the same as that of Example 18, which was a good result. The results are shown in Table 3.
[0177] Even when the laminated bodies of Examples 1 to 25 were bent, the active energy ray-curable adhesive layer did not break or crack, and the active energy ray-curable adhesives 1 to 16 had the flexibility of a cured film. On the other hand, when the laminated body of Comparative Example 2 was bent, the active energy ray-curable adhesive layer broke and cracked, and the active energy ray-curable adhesive 18 did not have the flexibility of a cured film.
[0178]
[0179] Table 3
[0180]
Claims
1. An active energy ray-curable adhesive comprising a mono- to tetra-functional (meth)acrylate (A) having a tertiary amino group, a polyol compound (B), and a polyisocyanate compound (C).
2. The active energy ray-curable adhesive according to claim 1, wherein the (meth)acrylate (A) is represented by the structural formula (1): in, R 1 Represents H or methyl, R 2 represents a monovalent organic group having a (meth)acryloyl group, R 3 and R 4 Each independently represents a monovalent hydrocarbon group or a monovalent organic group containing a heteroatom. 3 . The active energy ray-curable adhesive according to claim 1 , wherein the (meth)acrylate (A) has an amine value of 80 mgKOH / g or more. 4 . The active energy ray-curable adhesive according to claim 1 , wherein an acryl equivalent of the active energy ray-curable adhesive is 300 g / eq or more and 1000 g / eq or less. 5 . The active energy ray-curable adhesive according to claim 1 , wherein the (meth)acrylate (A) is contained in an amount of 10% by mass or more and 40% by mass or less in the active energy ray-curable adhesive. 6 . The active energy ray-curable adhesive according to claim 1 , wherein the (meth)acrylate (A) has a hydroxyl group.
7. The active energy ray-curable adhesive according to any one of claims 1 to 6, wherein the (meth)acrylate (A) is represented by the structural formula (2) or (3), in, R 1 Represents H or methyl, R 2 It represents a monovalent organic group having a (meth)acryloyl group.
8. The active energy ray-curable adhesive according to any one of claims 1 to 6, wherein the (meth)acrylate (A) is represented by structural formula (4): in, X represents a nitrogen atom or a carbon atom, R 1 Represents H or methyl, R 2 represents a monovalent organic group having a (meth)acryloyl group, R 3 and R 4 Each independently represents a monovalent hydrocarbon group or a monovalent organic group containing a heteroatom; R 3 and R 4 Independently of each other or together they form a cyclic group. 9 . The active energy ray-curable adhesive according to claim 6 , wherein the (meth)acrylate (A) has a weight average molecular weight of 3,000 to 100,000. 10 . The active energy ray-curable adhesive according to claim 1 , comprising a polyfunctional (meth)acrylate (D) having a weight average molecular weight of less than 3,000 and containing no amino group. 11 . The active energy ray-curable adhesive according to claim 1 , wherein the total content of the polyol compound (B) and the polyisocyanate compound (C) is 50% by mass or more.
12. The active energy ray-curable adhesive according to any one of claims 1 to 11, comprising a compound (E) having a carboxyl group and having a weight average molecular weight of 3,000 or more and 100,000 or less, wherein the number of moles of the carboxyl group derived from the compound (E) is n c (E) The number of moles of amino groups derived from the (meth)acrylate (A) a (A) ratio n c (E) / n a (A) is 0.01 or more and 0.50 or less. 13 . The active energy ray-curable adhesive according to claim 1 , wherein the compound (E) has a (meth)acryloyl group and / or a vinyl group. 14 . The active energy ray-curable adhesive according to claim 1 , which does not substantially contain a solvent or a diluent.
15. A method for manufacturing a laminate, which comprises a lamination step, an irradiation step, and a aging step in sequence, wherein the lamination step uses the active energy ray-curable adhesive described in any one of claims 1 to 14 to bond the same or two or more films to each other to form a laminate film, the irradiation step irradiates the laminate film with active energy rays, and the aging step performs aging.
16. A method for manufacturing a laminate, which comprises, in sequence, a coating step, an irradiation step, a lamination step, and an aging step, wherein the coating step is to coat the active energy ray-curable adhesive described in any one of claims 1 to 14 on a film, the irradiation step is to irradiate the film coated with the adhesive with active energy rays, the lamination step is to bond the film coated with the adhesive with films of the same or different types to form a laminated film, and the aging step is to perform aging. 17 . The method for producing a laminate according to claim 15 , wherein the surface of the film is subjected to a corona treatment.
Citation Information
Patent Citations
Nuclear reactor vessel
JP1981057990A
Adhesive composition curable with active energy ray, method for forming laminate film using the same, and laminate film
JP1996253736A